Internet of things energy, industry, and healthcare - Rana, Arun Kumar; Salau, Ayodeji Olalekan; Sharma, Sharad; Tayal, Shubham; Gupta, Swati (CRC Press, 2022)
"This book provides future research directions in energy, industry, and healthcare domain, and explores the different applications of IoT and its associated technologies. The book discusses software architecture, middleware, data processing and management as well as security, sensors and algorithms
Includes bibliographical references and index
Keywords: Internet of things; Aufsatzsammlung